Mitigation of power system small signal oscillation using posicast controller and evolutionary programming - Mirfendereski, Shojaeddin; Abdul Wahab, Noor Izzri; Jasni, Jasronita; Othman, Mohammad Lutfi (School of Engineering, Taylor’s University College, 2014)
This research work explores the effect of posicast controller on mitigation of small signal oscillatory stability. Power system stabilisers (PSS) are a prevalent means to enhance the damping of oscillation in power system. However, sometimes the PSS could not perform its task and itself will be the cause of instability by producing negative damping. In this study, posicast is adopted as a rule of action which could be taken on any dynamic system. Tuning parameters is calculated by inherent characteristic of the system which also indicates the place that the posicast is needed. Also, evolutionary programming is used to optimise the performance of posicast for each dominant state. The New England 392Bus Test System is chosen to evaluate the performance of the controller. Improvements in rotor angle, generators active power, generators terminal voltages and system frequency have been observed.